The future of diagnostic laparoscopy - Cons - Sarah Simko; Kelly N Wright (Bioscientifica, 2022)
Endometriosis has a large impact on the lives of patients, affecting nearly 90% of women with chronic pelvic pain and infertility. Unfortunately, diagnosis for this condition is often delayed by an average of 7 years, with adolescent patients experiencing disproportionate delays. This is in part due to the use of an invasive procedure for primary diagnosis and limited access to subspecialty care. While laparoscopy serves an important purpose in the diagnosis and management of endometriosis, it has been found to be less cost-effective than empiric medical therapy and puts an emphasis on the lesion as opposed to the patient and the disease process as a whole. As studies emerge, we gain a deeper understanding of the complex nature of this disease. Laparoscopy has been shown to have variable results, with high recurrence rates and varying improvement in symptoms over time. Additionally, studies have shown a poor correlation between patients' pain and the stage and location of lesions, with laparoscopy showing greater benefit for later-stage disease and deep infiltrating endometriosis. This article seeks to evaluate the current standards for the management of endometriosis, discuss the place for diagnostic laparoscopy, and review future directions and alternatives.